The Analysis of Corporate Governance on Non-Performing Loans: Evidence from Indonesia - Ramadhanti, Jovita; Butar Butar, Ivan Destian; Pangaribuan, Christian Haposan (APPS Publications, 2021)
Objective – This study aims to know the impact of corporate governance mechanisms on the non-performing loan of a bank. This study also aims to analyze which corporate governance aspects are significant to the banks’ non-performing loans in Indonesia. Another objective of this study is to examine whether the relationship between corporate governance and non performing loan depends on bank ownership. This study’s corporate governance variables are the board size, board independence, and bank ownership category. This study focuses on the non-performing loan of the banks in Indonesia. Methodology – This study will examine 26 banks in Indonesia listed on the Indonesian Stock Exchange (IDX). It includes both foreign-owned (foreign bank) and domestic banks. The length of the period of observation is seven years, from 2012 to 2018. Panel data of these banks are analyzed using the fixed-effect regression. Findings – The regression result shows that board size and bank ownership category have no significant impact on the non-performing loan, while the board independence impacts non-performing loans negatively. Novelty – This study contributes to the academic literature, specifically on the issue of corporate governance in the banking sector. This study’s result and findings could be used as the reference for other studies and further research on the corporate governance issue. This study will also expand the literature about corporate governance in the Indonesian banking sector since there are still a limited number of studies that discussed this specific matter.